2022
DOI: 10.1002/ldr.4287
|View full text |Cite
|
Sign up to set email alerts
|

Soil salinity inversion in coastal cotton growing areas: An integration method using satellite‐ground spectral fusion and satellite‐UAV collaboration

Abstract: Soil salinity is a crucial factor in agriculture, rising salinity undermines cotton (Gossypium spp.) production in coastal areas of China and damages crops in other countries. In this study, we propose an effective integration method using satellite‐ground spectral fusion and satellite‐unmanned arial vehicle (UAV) collaboration for soil salinity monitoring in cotton growing areas. Firstly, an extreme learning machine (ELM), random forest (RF), and extreme gradient boosting (XGBoost) models were constructed bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…What’s more, the leverage of massive data brought by remote sensing has also made ML more widely used. For example, a study ( Qi et al., 2022 ) has proposed a soil salinity monitoring method based on satellite-ground spectral fusion and satellite-UAV collaboration in cotton planting areas, thereby drawing a soil salinity distribution map for cotton fields. In this study, we establish a method to predict soil salinity, EC, seed yield, lint yield and ET based on four ML methods (GBDT, RF, XGBR, stacking ensemble model) and soil data, meteorological data, irrigation data and other data.…”
Section: Discussionmentioning
confidence: 99%
“…What’s more, the leverage of massive data brought by remote sensing has also made ML more widely used. For example, a study ( Qi et al., 2022 ) has proposed a soil salinity monitoring method based on satellite-ground spectral fusion and satellite-UAV collaboration in cotton planting areas, thereby drawing a soil salinity distribution map for cotton fields. In this study, we establish a method to predict soil salinity, EC, seed yield, lint yield and ET based on four ML methods (GBDT, RF, XGBR, stacking ensemble model) and soil data, meteorological data, irrigation data and other data.…”
Section: Discussionmentioning
confidence: 99%
“…This study introduced the concept of the RE band. Building upon its strong correlation with the spectral attributes of vegetation canopies and its sensitivity to soil salinity [30], the spectral index was enhanced using the RE band to accomplish soil salinity inversion beneath vegetation cover. During the correlation analysis between single-band reflectance and SSC, it was observed that the absolute correlation coefficient of the red-edge spectral indices, including the RE band, ranged from 0.50 to 0.55.…”
Section: Re Band Of Uav Remote Sensing Utilized For Soil Salinity Inv...mentioning
confidence: 99%
“…The SRF-CC is more suitable for handling non-uniform relationships caused by differences in reflectivity by integrating each band interval separately. The simulation of ground spectral data and spatial data such as Sentinel-2A and GaoFen-6 (GF-6) has successfully achieved spatial inversion of fractional vegetation cover (FVC), soil salinity, and chlorophyll content [20][21][22][23]. However, further exploration is needed to determine the applicability of the SRF-CC in studying of the CNC in apple orchards.…”
Section: Introductionmentioning
confidence: 99%